Costo de producción en la microempresa de confecciones Sport JC del Cantón Valencia - Provincia de los Ríos, año 2021 - Castro De La Cruz, Tatiana Mercedes (2022)
The present research work entitled: Cost of production in the micro-enterprise of confections Sport JC of the canton Valencia - Province of Los Ríos, the year 2021, is carried out to evaluate the costs within the micro-enterprise Sport JC in the manufacture of sportswear, using the system of production orders. For this purpose, a documentary bibliographic research is used to structure the theoretical framework, it is descriptive because it describes the basic characteristics of the costs by production order and its elements, the inductive-deductive methods, and synthesis analysis for the management of the information and the issuance of conclusions. As techniques and interview through its instrument, the questionnaire is applied to the manager of the microenterprise to know all the information related to the elements of the cost and the production processes that occur in the elaboration of sportswear. The population consisted of the employees of the microenterprise. Among the main results, the unit cost for the production of T-shirts was $5.60, with a profit of $2.40 per T-shirt, which shows that the profit margin was 42.83%; for warmers, the unit cost was $8.89, with a profit of $3.11 per garment, with a profit margin of 34.92%; finally, the total unit cost for shorts was $5.16, with a profit of $1.84, which shows a profit margin of 35.74%.